ANALISIS PENGARUH KUALITAS PELAYANAN, HARGA, DAN FASILITAS TERHADAP KEPUASAN PASIEN RAWAT JALAN DI RUMAH SAKIT KARIADI SEMARANG - Supriyanto, Yuda; Soesanto, Harry (Faculty of Economics and Business Diponegoro University, 2012)
The services sector, especially health services experienced significant growth and has good prospects. This condition makes the competition become more progressively tight. Every hospital should be able to use a variety of ways in order to attract patients through the quality of service. Society tends to demand fast and better healthcare service. Many hospital are aware of it, so they have to achieve that customer satisfaction in a variety of strategies to retain customers. The aim of this research is to analyze the effect of quality of service, price and facilities to the satisfaction of outpatients. This research was based by the number of outpatient‘s complaints are decreased at Kariadi's Hospital, and to know the influence of quality of service, price and facilities to the satisfaction of outpatients at Kariadi’s Hospital. The population in this research were outpatients of Kariadi’s Hospital. The number of samples used in this research are 100 people. Data was collected through questionnaire by purposive sampling technique. Data analysis technique used is multiple linear regression analysis to determine the influence of the variable quality of services, price and facilities to the satisfaction of outpatients at Kariadi’s Hospital. The analysis showed that the variable quality of service, price and facilities have a significant positive effect on customer satisfaction variables, both individually and together. The amount of Adjusted R Square is 0.836. This means that 83.6% variation in customer satisfaction can be explained by the three independent variables of service quality, price, and facilities. While the rest can be explained by other variables outside of the study.